2019
DOI: 10.21608/edj.2019.72615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inlay preparation design on the trueness of different impression techniques

Abstract: Statement of problem. Limited data is available on the effect of inlay preparation design on the trueness of digital impressions obtained by intra-oral scanners and conventional impressions. Purpose. The purpose of this study was to evaluate the influence of inlay preparation design on the trueness of different impression techniques Material and methods. Two typodont resin teeth representing maxillary first premolars were prepared for disto-occlusal inlay preparations with two different divergent angels (6° an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The active triangulation strategy used in Omnicam IOS could have better trueness results if the scanning and oral conditions are ideal. In comparison, the confocal microscopic technology used in Trios doesn't need a certain distance for focusing, and therefore it's unnecessary to make the scanner tip attached to the teeth during the scanning procedure (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active triangulation strategy used in Omnicam IOS could have better trueness results if the scanning and oral conditions are ideal. In comparison, the confocal microscopic technology used in Trios doesn't need a certain distance for focusing, and therefore it's unnecessary to make the scanner tip attached to the teeth during the scanning procedure (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Jeon et al (22) mentioned that increasing wall divergence will lead to better trueness results. Attia M (20) et al concluded that inlay preparation with 12 degrees axial wall divergence is significantly better than the 6 degrees axial wall divergence, in terms of trueness. The second null hypothesis was rejected as there was a difference in trueness and precision between the different Endocrown preparations.…”
Section: Discussionmentioning
confidence: 99%